Towards inflation targeting in Egypt fiscal and institutional reforms to support disinflation efforts - Abdel-Ghaffar, Youssef H.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
This paper reviews the prerequisites of inflation targeting, analyses the extent to which they are met in Egypt and examines whether the Egyptian economy, under its current status, is ready to formally adopt an inflation targeting regime. It discusses why developing strong fiscal, financial and monetary institutions is so critical to the success of inflation targeting and explains how, even if the prerequisites are not stringently fulfilled in the beginning of its adoption, the move towards them is believed to contribute to the macroeconomic stability of the country. More particularly, the focus is being put on fiscal balance, the financial sector and central bank independence. Since we believe that the latter is the most important condition in the inflation targeting implementation process, the paper discusses the CBE's independence and underlines the importance of issues related to transparency, credibility, technical capabilities and accountability. Finally, the paper draws some conclusions and formulates some policy recommendations on the adjustments the country should put in place in order to ensure a successful transition towards an inflation targeting regime.
Economic Papers